Pengaruh Keselamatan Kerja, Kesehatan Kerja, dan Sistem Manajemen K3 terhadap Kinerja Karyawan UD. Berkah Mandiri - Alfa Nurdiana; Heru Sutapa; Indah Yuni Astuti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This research was conducted with the primary objective of examining and determining the effect of occupational safety, occupational health, and the Occupational Health and Safety Management System (OHSMS) on employee performance at UD. Berkah Mandiri, located in Kediri Regency. The background of this study is based on the importance of implementing OHS in the workplace as an effort to minimize the risk of accidents, improve employee well-being, and support overall company productivity. In today’s increasingly competitive industrial world, attention to occupational safety and health is a key factor that not only protects workers but also enhances organizational efficiency and effectiveness. The research method employed was a quantitative approach with an associative research design. The population consisted of 56 employees, all of whom were taken as respondents through a saturated sampling technique. Data were collected using a questionnaire instrument constructed based on indicators of occupational safety, occupational health, OHSMS, and employee performance. The data were then analyzed using SPSS version 25.0 through validity and reliability tests, multiple regression analysis, and hypothesis testing both partially and simultaneously. The results of the analysis revealed that occupational safety has a significant effect on employee performance, indicating that the better the implementation of safety standards, the higher the performance achieved. Similarly, occupational health was found to have a positive and significant effect on employee performance, suggesting that healthy working conditions contribute to higher motivation and work effectiveness. Furthermore, the OHSMS also significantly influenced employee performance, reflecting that proper policies, procedures, and supervision in OHS management create a safe and productive work environment. Collectively, the three variables—occupational safety, occupational health, and OHSMS—were proven to have a significant simultaneous effect on employee performance at UD. Berkah Mandiri. Thus, this study emphasizes that occupational safety, occupational health, and OHSMS are crucial factors that must receive serious attention in order to improve employee performance and support sustainable business continuity.